Characteristics of Optically Thin Coastal Florida Cumuli Derived From Surface‐Based Lidar Measurements. Issue 18 (24th September 2018) - Delgadillo, Rodrigo; Voss, Kenneth J.; Zuidema, Paquita
Abstract: The optical depths and sizes of optically thin passive shallow cumuli are characterized with a micropulse lidar. The measurements are from a coastal south Florida location spanning a 10‐week synoptically suppressed winter time period with almost no upper‐level clouds present. Clouds are distinguished from aerosol through visual comparison to zenith‐viewing time‐lapse camera images, establishing an instrument‐specific particle backscatter coefficient threshold. Sun photometers provide a continuous independent aerosol optical depth estimate applied within the lidar retrieval of cloud optical depth. The focus is on clouds that do not attenuate the lidar signal. Clouds with optical depths less than one constitute more than 13% of the sampled data set, with decreasing optical depths occurring more frequently. Most of the clouds are less than 60 m thick and are located below 1 km. The optically thin regions occur most frequently in individual 15‐s samples, corresponding to a horizontal width of less than 100 m, with occasional stratiform segments extending up to 2 km. Many segments border optically thicker regions, but some are self‐contained, reflecting small‐scale humidity variations near‐saturation. To our knowledge, this study is the first to apply micropulse lidar data toward characterizing these low, shallow, broken clouds, too small for robust characterization from space but whose ubiquitiousness renders them radiatively important. Key Points: Optical depth and sizes of small shallow cumuli are characterized by a micropulse lidar during a 10‐week period Thirteen percent of sampled clouds have optical depths <1. These clouds typically reside below 1 km and are <60 m thick and <100 m wide These radiatively important clouds are too small for robust characterization from space